BUDD-CHIARI SYNDROME IN BEHCET'S DISEASE: A RETROSPECTIVE MULTICENTER STUDY - Akyol, L.; Toz, B.; Bayindir, O.; Zengin, O.; Cansu, D. Uskudar; Yigit, M.; Sayarlioglu, M. (Bmj Publishing Group, 2017)
[Abstract Not Available]
Annual European Congress of Rheumatology -- JUN 14-17, 2017 -- Madrid, SPAIN